A Socially Responsible Trade: An Analysis of Ethical Discourse in Editor & Publisher, 1930-1934. - Fuller, Max (American Journalism)
In the 1930s, the pages of Editor & Publisher were filled with nuanced stories revealing the many ethical challenges facing journalism amid the economic woes of the Great Depression, increased public scrutiny over news, and the influence of New Deal policies on journalistic practices in the US. Industry insiders discussed everything from how to best report criminal activities and sports to how to best write about the nation's economic plight all while keeping the public's interest in mind. Analysis of 265 E&P issues, published between 1930 and 1934, found that reporters of the day were highly concerned about ethics in the professional practice of journalism during a time when the newspaper industry faced challenges such as outside scrutiny, governmental critique, and diminished public support. It will be argued that these ethical conversations among journalists promoted functions of a press system outlined by the Social Responsibility Theory of the Press more than a decade before its adoption by the Hutchins Commission in 1947.